VIDEO DEVELOPMENT OF VARIETY OF DANCE MOVEMENTS TO FACILITATE TEACHERS IN THE PROCESS OF CREATING DANCE ARTS - Novi Agung Aryudanto (PROGRES PENDIDIKAN, 2023)
The development of learning media in the form dance Movement Videos as an effort to facilitate teachers in the process of creating dance works is based on several factors, including: 1) being affected by the Covid-19 pandemic, 2) the ability of dance teachers who are not yet qualified in cerating dance works, 3) and the absence of dance learning media, so the development of learning media in the form of videos of various dance moves at SDN Palang. Based on the problems that have been described, the development aims to produce a valid Variety of Dance video media for teachers at SDN Palang. The development of this video media uses the ADDIE model with five stages including: 1) needs analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The Evaluation of the video media of various dance movments was carried out by media experts, educators as users and students of SDN Palang. The results of the research on the development of video media for various dance movements showed that the percentage obtained from the validation results of media experts with a score of 90 % was included in the very valid category and was suitable for use without revision. The results of material expert validation get a score of 75 % which is included in the very valid category and is suitable for use without revision. Judging from the response as many as 7 educators have an average of 85.57 %. Meanwhile, from the responses, 5 students had an average of 86.7 %. This means that educators and students give a positive response, then the high percentage proves that the media is said to be effective and acceptable